Of the Novel-Testimony as a Genre - Jiménes Estrada, Camilo (Íkala, Revista de Lenguaje y Cultura, 1998)
At present, two conceptions coexist in the field of literary theory regarding genres and their applicability to the study of the work: one considers them obsolete categories, typical of anachronistic professors and schools guided by prescriptive and normative tendencies. The other considers that genres are still valid, insofar as they place the work in a tradition, which makes it possible to ponder the specificity of that work within the ensemble in which it is inscribed. For Mikhail Bakhtin (1989), for example, who has made a lucid study of the subject in order to define the novel, "The study of the text cannot [...] be satisfactorily carried out without first having elucidated its generic keys and, consequently, the tradition in which it is inserted" (Huerta Calvo, 1994: 142).